Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

3t - 7 = 5t, then 6t =

Sagot :

First, you would need to solve for t using the equation: 3t - 7 = 5t
Move all the numbers with variable on ones side
-7 = 5t - 3t
Combine like factors
-7 = 2t
Solve for t
-7/2 = t
After solving for t, you plug the answer into the equation you want to solve.
6 (-7/2) = -21
6*-7 = -42
-42/2 = -21
The answer is -21
3t-7=5t
so add 7 to both sides
3t=5t+7
-5t   -5t
-2t=7
/-2   /-2
t=-3.5
6t=
6(-3.5)
-21